A Systematic Literature Review for Distinguishing Tax Terms: Equality, Equity, Justice, and Fairness - Susilawati, Neni; Gunadi; Rahayu, Ning (Journal of Economics and Behavioral Studies, 2022)
The organizational fairness literature is frequently used by fairness scholars to evaluate tax fairness models, conceptions, and measurements, even though tax fairness and tax justice are context-dependent and require further formulation. However, the generalizability of organizational justice studies to other domains and the extent to which context affects justice perceptions remain unknown. There is a dearth of literature that defines the terms tax fairness, tax equity, tax equality, and tax justice accurately. The purpose of this research is to distinguish between the tax phrases "fairness," "equity," "equality," and "justice." Additionally, the author refined the tax words inside the operationalized idea to produce more precise measures for future research. A systematic literature review was conducted as the research method, utilizing the PRISMA research approach and NVivo for qualitative data processing. As a result of the research findings, the phrase "tax fairness," which was previously believed to refer to a lesser degree of tax justice than "tax equity," is now used to refer to tax justice in a broader sense. Tax equity has the most extensive set of characteristics and indicators. Meanwhile, the word "tax justice" refers to a more specialized area of law and procedure, namely tax law. The phrase "tax equity" is included in the indicator "tax fairness," although the term "tax equality" is rarely used in the worldwide tax literature. The more distinct the tax terms, the easier it will be for the tax researcher to use terms like tax fairness, tax justice, tax equity, and tax equality correctly.